UPAYA MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN BIOLOGI MELALUI MODEL PROBLEM BASED LEARNING (PBL) PADA SISWA KELAS XI MIA3 SMA NEGERI MEGANG SAKTI - Temu Sugiani (Program Studi Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Sriwi, 2018)
To achieve the goal of education maximally, the role of teachers is very important and expected teachers have a good way / model of teaching and able to choose the appropriate learning model and in accordance with the concepts of subjects to be delivered. The purpose of this action research is to improve the learning result of biology of respiratory system materials using Problem Based Learning (PBL) model in XI MIA3 students of SMA Negeri Megang Sakti. This research uses class action research (action research) as much as 2 cycles. Each cycle consists of four stages: planning, implementation, observation and reflection. Target of this research is student of class XI MIA3 SMA Negeri Megang Sakti. The data obtained in the form of formative test results and observation sheet of teaching and learning activities. From the analysis result, it is found that the students' learning outcomes have increased from cycle I to cycle II, that is, the average learning cycle (65,95) and learning completeness (71,8%) increase to mean of learning result (73,85) and learning mastery (87,18%) in cycle II. The conclusion of this research is the model of Problem Based Learning (PBL) can improve student learning result of class XI MIA3 State Senior High School Megang Sakti and Problem Based Learning (PBL) model can be used as one of alternative of Biology learning.Keywords : Learning Result, Biology, Problem Based Learning (PBL)